ORAL TOPICAL TIMOLOL MALEAT OR ORAL PROPRANOLOL TREATMENT FOR INFANTILE HEMANGIOMAS: CLINICAL ANALYSIS OF 403 PATIENTS - Terzi, Özlem; Arslantaş, Esra; Baş, Nur Cennet; Kaçar, Gonca Ayşe; Uysalol, Pasli Ezgi; Solgun, Avni Hüseyin; Yıldırgan, Duygu; Karagenç, Özkan Ayşe; Ertürk , Saide; Ayçiçek, Ali (Sanamed, 2023)
Objective: Infantile hemangiomas (IH) are the most common benign vascular tumors of infancy. Propranolol (P), a nonselective beta-blocker, has been successfully used in managing IHs. Ongoing studies investigate the efficacy of the topical β-antagonist timolol maleate (TM) in IHs. The aim of this study is to assess the effects of interventions for managing infantile hemangiomas in children.Material and Methods: We retrospectively reviewed a total of 403 IH patients from March 2021 to March 2022. The patients were stratified into three groups. Patients in Group 1 were given TM at a dose of one drop topically twice a day, 0.5%. Patients in Group 2 were given P at a dose of 1 mg/kg twice a day. The patients in Group 3 did not receive any treatment, and observation was conducted solely by contacting the controls.Results: The median age of diagnosis was 5 months (range 0-60), with 57.1% of the cases being male. While TM treatment was applied to 32% of the children and P treatment was applied to 46.9% of the children, no treatment was administered in 21.1%. The most common location of hemangiomas was the face, accounting for 39.2%. Hemangiomas were observed in more than one location in 48 (12%) children. The median follow-up period for the patients was 4 months (range 0-28). Hemangiomas remained unchanged in 28.3% of all cases, shrank in 60.3%, and continued to grow in 11.4%. The primary indication for initiating TM was superficial hemangiomas and infants younger than 6 months. The leading reason for starting P significantly higher than in the other groups (p:0.001). No statistically significant differences were observed between the groups regarding bleeding and ulceration rates (p>0.05).Conclusion: The efficacy of propranolol in treating IH was higher than that of TM.
Keywords: timolol maleate; infantile hemangioma; propranolol